Conceptual and applied aspects of cross-cultural models of civilisational identity - Liahchylin, Anatoly A.; Vorobyova, Svetlana V. (Journal of the Belarusian State University. Sociology, 2026)
The article reveals the conceptual and applied aspects of cross-cultural models of civilisational identity. Singular and pluralistic models of essentialist and constructivist identity are substantiated. The conceptual differences between four types of cross-cultural models are revealed and the possibilities and limits of their applicability are determined. Singular models of essentialist identity are focused on developing universal criteria, pluralistic models – on developing universal criteria on given scales. Singular models of constructivist identity are focused on finding conditions for commensurability of cultures, pluralistic models – on finding conditions for coexistence of incommensurable cultures.
Keywords: civilisational identity; singular models of identity; pluralistic models of identity; essentialist identity; constructivist identity